Brain dysfunction as one cause of CFS symptoms including difficulty with attention and concentration - Natelson, Benjamin H. (Frontiers in Physiology, 2013)
We have been able to reduce substantially patient pool heterogeneity by identifying phenotypic markers that allow the researcher to stratify chronic fatigue syndrome (CFS) patients into subgroups. To date, we have shown that stratifying based on the presence or absence of co-morbid psychiatric diagnosis leads to a group with evidence of neurological dysfunction across a number of spheres. We have also found that stratifying based on the presence or absence of comorbid fibromyalgia leads to information that would not have been found on analyzing the entire, unstratified patient group. Objective evidence of orthostatic intolerance may be another important variable for stratification and may define a group with episodic cerebral hypoxia leading to symptoms. We hope that this review will encourage other researchers to collect data on discrete phenotypes in CFS to allow this work to continue more broadly. Finding subgroups of CFS suggests different underlying pathophysiological processes responsible for the symptoms seen. Understanding those processes is the first step toward developing discrete treatments for each.